Lonomia obliqua Caterpillar Spicules Trigger Human Blood Coagulation via Activation of Factor X and Prothrombin - Donato, José L.; Moreno, Ronilson A.; Hyslop, Stephen; Duarte, Alaor; Antunes, Edson; Le Bonniec, Bernard F.; Rendu, Francine; Nucci, Gilberto de (Thrombosis and Haemostasis, 1998)
In southern Brazil, envenomation by larvae of the moth Lonomia obliqua (Walker) may result in blood clotting factor depletion, leading to disseminated intravascular coagulation with subsequent haemorrhage and acute renal failure which may prove fatal. We have examined the effect of a crude extract of spicules from these caterpillars on in vitro hemostasis. The extract alone did not aggregate platelets and had no detectable effect on purified fibrinogen, suggesting that extract induces clot formation by triggering activation of the clotting cascade. In agreement with the presence of thrombin-mediated activity, hirudin prevented clot formation. The extract was found to activate both prothrombin and factor X, suggesting that the depletion of blood clotting factors results from the steady activation of factor X and prothrombin. Heating and diisopropylfluorophosphate abolished the procoagulant activity of the extract, indicating that the active component involved is a protein that may belong to the serine protease family of enzymes. The ability of hirudin to inhibit this coagulant activity suggests that this inhibitor could be beneficial in the treatment of patients envenomed by L. obliqua caterpillars.